Peer Assessment and Video Feedback for Fostering Self, Co, and Shared Regulation of Learning in a Higher Education Language Classroom - Clayton Bernard, Rebecca; Kermarrec, Gilles (Frontiers in Education, 2022)
Self-regulated learning includes the cognitive, metacognitive, behavioral, motivational, and affective aspects of learning. The conceptualization of self and socially regulated learning has recently received much attention and peer assessment has been found to increase the use of metacognitive activity. The present exploratory qualitative study aimed to identify self-, co-, and socially shared regulatory processes in an oral English as a Foreign Language task. The regulatory activity deployed by 10 learners was studied within the context of a peer assessment task using an assessment form paired with video feedback in the context of an English language classroom at a French university. These interactions were filmed and discussed in individual self-confrontation interviews which were analyzed through inductive coding. Specific findings from the classroom setting shed light on existing gaps in the literature. First, students can gain confidence in their own skills through assessing their peers and activating regulatory processes both individually and as a group. Second, appropriate tools can increase co-regulated and socially regulated learning through the structuring of cooperative regulatory behaviors. Third, psychological safety appeared to be a propitious social context for supporting regulated learning (SRL, CoRL, and SSRL). We also shed light on the fact that adaptive regulatory strategies are present in oral (as well as written) English as a Foreign Language tasks. These results indicate the potential for learning situations based on video feedback used in conjunction with peer assessment and collaborative learning in order to develop regulatory behaviors in language learners.